1995
DOI: 10.1152/ajpheart.1995.268.4.h1694
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced alterations of neurogenic constriction and dilation of human uterine artery

Abstract: The responses to electrical field stimulation (EFS) of perivascular nerves in human uterine arteries were characterized. The arteries were removed from pregnant and nonpregnant patients undergoing hysterectomy. Tetrodotoxin, guanethidine, and phentolamine blocked EFS (2 min, 80 V, 0.1-ms duration)-induced constriction. The constrictions and the endogenous norepinephrine levels were lower (P < 0.01) in uterine arteries from pregnant than from nonpregnant patients. When arterial rings were precontracted, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…Atropine, ␤-adrenoceptor antagonists, indomethacin, and endothelium-denudation failed to inhibit the response, which was however abolished by oxyHb. The neurogenic, NO-mediated relaxation was greater in the uterine artery from pregnant patients undergoing hysterectomy than that from nonpregnant patients (Nelson et al, 1995b). In the guinea pig artery, high frequency stimulation (Ͼ5 Hz) also liberates vasodilator peptides (Morris, 1993), but this does not seem to be the case in the other mammals.…”
Section: E Uterine Vasculaturementioning
confidence: 90%
See 1 more Smart Citation
“…Atropine, ␤-adrenoceptor antagonists, indomethacin, and endothelium-denudation failed to inhibit the response, which was however abolished by oxyHb. The neurogenic, NO-mediated relaxation was greater in the uterine artery from pregnant patients undergoing hysterectomy than that from nonpregnant patients (Nelson et al, 1995b). In the guinea pig artery, high frequency stimulation (Ͼ5 Hz) also liberates vasodilator peptides (Morris, 1993), but this does not seem to be the case in the other mammals.…”
Section: E Uterine Vasculaturementioning
confidence: 90%
“…As described formerly, NO derived from vascular endothelium is not the sole endogenous NO participating in circulatory homeostasis. The presence of nitrergic nerves in human uterine arteries and female genital organs has been histologically determined Yoshida et al, 1995); and the intense neurogenic relaxation mediated by NO was observed in human Nelson et al, 1995b), monkey , dog (Okamura et al, 1995), and guinea pig uterine arteries (Morris, 1993). It would be quite intriguing to clarify the physiological role of nervederived NO in the regulation of uterine circulation in women with normal pregnancies and in patients with pre-eclampsia.…”
Section: Pre-eclampsia (Pregnant Intoxication)mentioning
confidence: 99%
“…Being responsible for adequate perfusion of the maternal-fetal interface, the uterine vasculature undergoes dramatic changes during pregnancy to ensure continuous blood supply and nutrients to the growing uterus and fetus. Substantial remodeling (5) and sympathetic denervation (35) of the uterine arteries, enhanced uterine vasodilatation (7,49), and reduced vascular tone (44) enable the uterine vasculature to act as a low-resistance shunt to accommodate a 20-fold increase in uterine blood flow during gestation.…”
mentioning
confidence: 99%
“…We have previously reported that acetylcholine is more potent and efficacious in producing dilation of isolated uterine arteries from pregnant than from nonpregnant patients. 6,7 The acetylcholine-induced relaxation was blocked by NO synthase (NOS) inhibitors and thus is apparently mediated by NO. 6,7 Furthermore, pregnancy-induced increases in basal NO production have been found in the uterine vasculature of rats, 8,9 guinea pigs, 10,11 and sheep.…”
mentioning
confidence: 99%
“…6,7 The acetylcholine-induced relaxation was blocked by NO synthase (NOS) inhibitors and thus is apparently mediated by NO. 6,7 Furthermore, pregnancy-induced increases in basal NO production have been found in the uterine vasculature of rats, 8,9 guinea pigs, 10,11 and sheep. 3,12,13 NO is produced by NOS, of which 3 isoforms have been identified: endothelial NOS (eNOS), neuronal NOS (nNOS), and inducible NOS (iNOS).…”
mentioning
confidence: 99%